2014
DOI: 10.1590/1516-1439.228213
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxide nanoparticles as additives for vegetable lubricants

Abstract: Currently, vegetable oils have been studied as biolubricants in order to reach new environmental standards. Besides being non-renewable, mineral oils from petroleum bring consequences to the environment due to its low biodegradability. Thus, the aim of this work is to develop a biolubricant and to add oxide nanoparticles (ZnO and CuO) in order to improve abrasion resistance and friction. This product must be biodegradable and has better performance under boundary lubrication. The methodology consisted of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 10 publications
2
27
0
1
Order By: Relevance
“…These results were mostly related to the presence of epoxy functions that are known to confer rigidity to the polymers chains (Yang et al, 2008). The current literature devoted to biolubricants based on epoxidized vegetable oils report that they exhibit high VI and are generally used in a wide temperature range due to their higher viscosity compared to the raw oil, especially at high temperature (Erhan and Asadauskas, 2000;Trajano et al, 2014). Our results are in total accordance with these observations.…”
Section: Mineral Lube Oilsupporting
confidence: 90%
“…These results were mostly related to the presence of epoxy functions that are known to confer rigidity to the polymers chains (Yang et al, 2008). The current literature devoted to biolubricants based on epoxidized vegetable oils report that they exhibit high VI and are generally used in a wide temperature range due to their higher viscosity compared to the raw oil, especially at high temperature (Erhan and Asadauskas, 2000;Trajano et al, 2014). Our results are in total accordance with these observations.…”
Section: Mineral Lube Oilsupporting
confidence: 90%
“…The use of oxide NPs (ZnO and CuO) as lubricant additives should be noted [97][98][99][100][101][102][103][104]. For example, biolubricants using vegetable oils (soybean and sunflower) with ZnO and CuO NPs as additives are biodegradable and have better performance in boundary lubrication.…”
Section: Metalsmentioning
confidence: 99%
“…Thus, for the sunflower bio-lubricant, it was observed that its density is little higher than the obtained for commercial sunflower oil. This increase is due to the epoxidation reaction, which modifies its physical and chemical properties 25 . The efficiency of the epoxidation reaction was determined by iodine index, a parameter used to indicate the presence of double bonds in a fatty acid ester, which corresponds to the number of centigrams of iodine absorbed per 1 gram of fat.…”
Section: Epoxidized Sunflower Oil Characterizationmentioning
confidence: 99%